Pendampingan Kajian Tafsir Juz Amma Tematik di Masjid Al-Ikhlas Madyopuro Kedungkandang Kota Malang - Rosidin (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2024)
Abstract This article is a report on mentoring the study of thematic Tafsir Juz 'Amma at the Masjid Al-Ikhlas Madyopuro, Kedungkandang, Malang City, which the author carries out every Wednesday, from May to August 2023, precisely after the Maghrib prayer until Isha' time. This mentoring activity uses the Service Learning (SL) method which has three main elements, namely Civic Engagement, Practical Experience and Academic Study. There are three findings: First, mentoring activities consist of two stages, namely the preparation (tahammul phase) and the delivery (ada’ phase). Second, the impact of this mentoring activity includes changes in cognitive, affective, and psychomotor domains of mentoring participants. Third, the mentoring activity for the study of thematic Tafsir Juz 'Amma is a variation of the Living Qur'an which is in harmony with Indonesian local wisdom. Because Juz 'Amma contains Chapters (Surah) that are familiar to the lives of Muslims in Indonesia. So, it has the potential to be replicated by lecturers who are entrusted with carrying out Qur’anic Interpretation studies in various mosques and other majelis ta’lim. Keywords: Mentoring, Tafsir Studies, Juz 'Amma. Abstrak Artikel ini merupakan laporan kegiatan Pendampingan Kajian Tafsir Juz ‘Amma Tematik di Masjid Al-Ikhlas Madyopuro Kedungkandang Kota Malang yang penulis lakukan setiap hari Rabu, bulan Mei hingga Agustus 2023, tepatnya setelah shalat Maghrib hingga masuk waktu Isya’. Kegiatan pendampingan ini menggunakan metode Service Learning (SL) dengan tiga unsur utama, yaitu Civic Engagement, Practical Experience dan Academic Study. Ada tiga temuan: Pertama, kegiatan pendampingan terdiri dari dua tahap, yaitu persiapan (fase tahammul) dan penyampaian (fase Ada’). Kedua, dampak kegiatan pendampingan ini meliputi perubahan domain kognitif, afektif, dan psikomotorik pada peserta pendampingan. Ketiga, kegiatan pendampingan Kajian Tafsir Juz ‘Amma Tematik menjadi salah satu variasi dari Living Qur’an yang selaras dengan kearifan lokal Indonesia. Dikarenakan Juz ‘Amma memuat Surat-Surat yang familiar dengan kehidupan umat muslim di Indonesia, sehingga berpotensi direplikasi oleh para dosen yang diberi kepercayaan untuk mengisi kajian tafsir di berbagai masjid, mushalla, dan majlis ta’lim lainnya. Kata Kunci: Pendampingan, Kajian Tafsir, Juz ‘Amma.